Soil erosion: A cause or a consequence? - Le, Du Van (Animo Repository, 2004)
Soil erosion is often a severe problem in sloping areas. It is attributed both to physical as well as human-induced factors, and results in onsite and offsite environmental damages. Because of this, maintaining agricultural productivity and environmental management in the uplands has always been a difficult task. As in other upland areas of Vietnam, there were dramatic land use changes in Bao Loc District, Central Highlands after the war. Consequently, there were rapid changes in the landscape and lifescape, especially the degradation of natural resources. In most areas in Bao Loc, agricultural growth is commonly associated with deforestation, soil erosion, and degraded watershed function.